Oxide-coated silicon nanowire array capacitor electrodes in room temperature ionic liquid - Qiao,L; Shougee,A; Albrecht,T; Fobelets,K (Electrochimica Acta, 2016)
Improved performance of Si nanowire arrays for capacitor electrodes in ionic liquid [Bmim][NTf2], is obtained by spin-on-doping the nanowires followed by hot, concentrated nitric acid oxidation. n- and p-type Si nanowire arrays are fabricated via a 2-step metal-assisted chemical etch process to increase the effective surface area. Spin-on-doping increases the doping density of the nanowires, enhancing the current by a factor of more than 3. The well-controlled HNO3 oxidation defines a thin, dense oxide layer on the Si nanowires increasing chemical stability, both expanding the electrochemical window and increasing the current further by a factor >2. Specific capacitances of 238 μF cm−2 (∼0.4 F g−1, 159 mF cm−3) and 404 μF cm−2 (∼0.7 F g−1, 269 mF cm−3) are obtained for n- and p-type Si nanowire arrays, respectively.